Constitution of the binary M-Sb systems (M = Ti, Zr, Hf) and physical properties of MSb2. (March 2018) - Tavassoli, A.; Grytsiv, A.; Failamani, F.; Rogl, G.; Puchegger, S.; Müller, H.; Broz, P.; Zelenka, F.; Macciò, D.; Saccone, A.; Giester, G.; Bauer, E.; et al.
Abstract: This study is closely related to the chemical interactions in thermoelectric joints of a hot metal electrode with p- and n-type skutterudite. As a result of this work, a first and complete phase diagram has been constructed for the TiSb system as well as partial phase diagrams (>65 at.% Sb) for the systems ZrSb and HfSb. Investigations are based on X-ray powder and single crystal analyses (determination of the crystal structure of Ti5 Sb8 with Zr2.6 Ti2.4 Sb8 -type, space group I 41 22; RF = 0.032), electron probe microanalyses (EPMA) and differential thermal analyses (DTA). Physical properties were evaluated for the binary compounds MSb2 (M = Ti, Zr, Hf) comprising electrical resistivity (from 4.2 K to 825 K), specific heat, thermal conductivity and thermal expansion coefficient (from 4.2 K to 300 K), Seebeck coefficient (from 300 K to 825 K) and elastic moduli at 300 K. These data will serve to evaluate the potential of MSb2 compounds (M = Ti, Zr, Hf) for thermoelectric devices, where these phases predominantly appear in the diffusion zones of the hot metal electrode with p- and n-type skutterudite. Graphical abstract: Highlights: The binary phase diagram TiSb was established between 600 °C and 1600 °C. Single crystal data were established for Ti5 Sb8 (Zr2.6 Ti2.4 Sb8 -type). Partial phase diagrams (>65 at.% Sb) were established for ZrSb and HfSb. Physical and mechanical properties have been derived for MSb2 (M = Ti, Zr, Hf).